'I would just like to be straight.' Boys and young men's concerns about being gay in the questions sent to a Finnish sexual counselling service - Spišák, Sanna; Vihlman, Maria (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
This article delves into the experiences of boys and young men grappling with anxiety surrounding potential 'homosexual' orientation, particularly within the context of societal expectations of normative heterosexuality. Using data from queries submitted to a Finnish sexual counselling service between 2017 and 2019, we highlight a dissonance between societal equality initiatives and the lived experiences of boys and young men in Finland. Drawing on queer theory and social norms critique, we analyse the constraints that limit the exploration of sexuality and self-identification among young Finnish men. Our findings underscore the pervasive impact of enduring societal norms on young men's ability to express their sexuality openly and authentically. We advocate for strategies to promote a more supportive environment for young persons to navigate their sexual identities and advocate for the well-being of young people, alongside considerations for professionals working in youth support roles.